Laughing at nothing : humor as a response to nihilism - Marmysz, John, 1964- (State University of New York Press, 2003)
"Disputing the common misconception that nihilism is wholly negative and necessarily damaging to the human spirit, John Marmysz offers a clear and complete definition to argue that it is compatible, and indeed preferably responded to, with an attitude of good humor. He carefully scrutinizes the phenomenon of nihilism as it appears in the works, lives, and actions of key figures in the history of philosophy, literature, politics, and theology, including Nietzsche, Heidegger, Camus, and Mishima. While suggesting that there ultimately is no solution to the problem of nihilism, Marmysz proposes a way of utilizing the anxiety and despair that is associated with the problem as a spur toward liveliness, activity, and the celebration of life."--Jacket
Keywords: Nihilism (Philosophy); Comic, The.; Nihilisme.; Comique.; nihilism.; PHILOSOPHY -- Movements -- Deconstruction.; PHILOSOPHY -- History & Surveys -- General.; Comic, The